SANKSI HUKUM ATAS KEJAHATAN MANIPULASI PENDAPAT AUDIT ATAS LAPORAN KEUANGAN EMITEN OLEH AKUNTAN PUBLIK DI PASAR MODAL - Yudana, I Made; Rudy, I Dewa Gde (Kertha Semaya : Journal Ilmu Hukum, 2013)
This paper entitled “legal sanction for a crime manipulation of opinion audits on the financial report of the issuer by the public accountant at the capital market”. The purpose of this writing is to know legal sanction for a crime manipulation of opinion audits on the financial report of the issuer by the public accountant at the capital market. A method of writing used is a method of writing law normative. The result is that legal sanctions imposed on the evil manipulation of opinion audits on the financial report of the issuer by the public accountant at the capital market is sanctions arranged in the provision of article 107 the act of no.8 1995 on capital market. Legal sanction for a crime manipulation of opinion audited by a public accountant besides regulated in the law no.8 of 1995 regarding regulated in the law on capital market also no. 5 2011 about public accountant, this matter will be assessed according to its the principle of lex specialis derogate legi generalis.
Keywords: Public Accountant, Audit Opinion, Legal Sanction, Capital Markets